Application of HTTP Filters to Manage Access to the Equipment in Automated Control Systems Based on the Technology of Industrial Internet of Things - Budnikov, K. I.; Serdyukov, O. V.; Kurochkin, A. V.; Nestulya, R. V. (Current Overview on Science and Technology Research Vol. 7, 2022)
One of the main factors for increasing the efficiency of the enterprise and reducing production costs is the use of new promising technologies. One of the most important among them now is the Industrial Internet of Things (IIoT). IIoT devices as the part of the manufacturing process collect and send to the cloud storage for further analysis a large amount of data that are directly related to the production, as well as the information about related factors. The engineering personnel has access to IIoT devices through the wireless devices. One of the ways of connection is the use of embedded web servers and HTTP communication protocol. The use of the secure connection mechanism via the HTTPS protocol for security purposes is not always possible or justified due to the increased consumption of computing resources. In this situation, one option to improve security would be to add an additional HTTP filter to restrict the access of mobile devices used to communicate with IIoT devices. With it, it is also possible to regulate the receipt of certain services that specific devices provide via the HTTP protocol. The article addresses HTTP filtering devices on Gridex-II hardware platform of the industrial type. The outcomes of their bench testing using conventional and enhanced filtering methods are shown.